2022
DOI: 10.1111/iwj.13775
|View full text |Cite
|
Sign up to set email alerts
|

Combination of fractional carbon dioxide laser and topical triamcinolone vs intralesional triamcinolone for keloid treatment: A randomised clinical trial

Abstract: To compare the therapeutic effect of fractional carbon dioxide (CO 2 ) laser + topical triamcinolone (TA) with intralesional TA on keloids. Twenty-two participants were randomised into two groups: group A, treated with fractional CO 2 laser + topical TA, and group B, treated with intralesional TA. The interventions were performed at every 4-week interval until the keloids were resolved or at the completion of 1 year. At each session, the scar volume, Vancouver Scar Scale (VSS) were assessed. Recurrence was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…22,23 In recent years, with the advancement of optoelectronic technology and a public focus on aesthetics, laser therapy has been widely used in clinical practice because of its advantages such as less trauma, faster recovery, and significant improvement in scar appearance. [24][25][26] Because of its low efficiency and high recurrence 95% CI: −1.17 to −0.63) were significantly improved after fractional CO 2 laser treatment for keloids, although vascularity did not significantly change. However, there was significant heterogeneity (I 2 = 98.0%, p = 0.000) in the analysis of vascularity, challenging the confidence in this aspect of our results.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…22,23 In recent years, with the advancement of optoelectronic technology and a public focus on aesthetics, laser therapy has been widely used in clinical practice because of its advantages such as less trauma, faster recovery, and significant improvement in scar appearance. [24][25][26] Because of its low efficiency and high recurrence 95% CI: −1.17 to −0.63) were significantly improved after fractional CO 2 laser treatment for keloids, although vascularity did not significantly change. However, there was significant heterogeneity (I 2 = 98.0%, p = 0.000) in the analysis of vascularity, challenging the confidence in this aspect of our results.…”
Section: Discussionmentioning
confidence: 98%
“…Although the summary results of this study show that fractional CO 2 laser monotherapy can effectively treat keloids, and more studies have revealed that fractional CO 2 laser combined therapy can significantly improve the efficacy of the treatment of keloids. Tawaranurak et al 24 discovered that the combination of fractional CO 2 laser treatment and topical triamcinolone resulted in a more significant reduction in scar volume compared to using topical triamcinolone alone for treating keloids (86.5% vs. 59.1%, p-value = 0.016). In addition, Sabry et al s study revealed that fractional CO 2 laser combined with 5-fluorouracil or verapamil hydrochloride can significantly reduce VSS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the 1-year follow-up results revealed recurrence rates of 9.1 and 18.2%, respectively. These results indicate that the combination of fractional CO 2 lasers and topical TAC may be an alternative treatment for keloids [ 75 ]. In addition, intralesional injections of TAC and desoxymethasone ointments were administered after uniform ablation using fractional Er:YAG lasers.…”
Section: Reviewmentioning
confidence: 99%